Female Graduate Students' Attitudes After Leadership Training. Issue 1 (June 2014) - Grantham, Susan; Pidano, Anne E.; Whitcomb, Jennifer M.
<x xml:space="preserve">Abstract</x> Although the increasing focus on female leadership in both the popular press and scholarly literature is relatively recent, women's leadership is not. Women have traditionally played a role in civic and cultural arenas and now have a greater opportunity to bring their particular leadership strengths to a broad range of organizations. The current paper reports on a case study about participants' attitudes after participating in a leadership seminar series program for female graduate students at a university in the Northeast. The program's design incorporated networking, goal setting, skills training, and mentoring. Postprogram results (N = 17) on measures of Houghton and Neck's Revised Self‐Leadership Questionnaire indicated significant changes on all three of the leadership questionnaire's dimensions as well as on several subscales within the dimensions indicating that after the leadership training, the women were adapting to more transactional practices such as self‐reward and goal setting.